Severe pulmonary hypertension in advanced aortic valve disease. Issue 11 (November 1978) - Basu, B; Cherian, G; Krishnaswami, S; Sukumar, I P; John, S
Abstract : Review of haemodynamic data of 151 cases with isolated aortic valve disease revealed severe pulmonary hypertension (pulmonary arterial systolic pressure of 60 mmHg or more) in 17 (11%). The left ventricular end-diastolic pressure was high in all but one case, suggesting that the severe pulmonary hypertension was a reflection of the late stages of aortic valve disease. The majority (64.7%) had a low cardiac index. Premature closure of the mitral valve was seen in 12 of the 17 patients. While the incidence of premature mitral closure was the same as in others with mild and moderate pulmonary hypertension, the average reversed ventriculoatrial gradient was higher in the latter groups.